The Influence of Training Methods and Agility Towards Futsal Dribbling Speed Result in High School Teams in Blora Regency - Pambudi, Satrio Rilo; Rahayu, Tandiyo; Rumini, Rumini (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2021)
Futsal is a complex sport because it requires special methods and tactics. Futsal is a version of the indoor soccer game that is recognized by the international governing body of association football, FIFA. The futsal sport itself has basic methods that must be developed to create a qualified game. This study aimed to analyze the difference in the influence of training methods in dribbling circuit and slalom dribble towards the dribbling speed of futsal players in high school teams in Blora Regency. The method of this study was quasi-experimental research that used a-two factor factorial design. The data that had been collected was arranged in a framework research design of 2x2 factorial. The population was 36 players of high school students in Blora Regency, the sample collection used purposive sampling. The study took 24 samples of players of high school students in Blora Regency. The result of the hypothesis test in the first research proved that there was a significant difference between the training methods in dribbling circuit and slalom dribbling towards the dribbling speed of high school male futsal players in Blora Regency. Blora. It was proved by ANOVA test with Fcount = 0,116 with a significant value of 0,037 with a significance level of 0,037 < 0,05. The second result of the hypothesis test showed that there was a different influence on students who had fast agility and slow agility towards the dribbling speed. It was supported by the result of ANOVA test with Fcount = 389,795 = 5.832 with a significance value of 0,000 with a significance level of 0,000 Ã‹â€š 0,05. The third result of the hypothesis test showed that there was an interaction between training methods and agility towards the dribbling speed in high school male futsal players in Blora Regency. The result of the analysis showed that there was an interaction between training methods and agility towards the speed of football dribbling in men's futsal team in Blora Regency. It was proved by ANOVA test with Fcount = 5.832 with a significance value of 0,025 with a significance level of 0,025 < 0,05. From the result of the analysis, it can be concluded that: there was a different influence between the training methods of dribbling circuit and slalom dribbling towards the dribbling speed of football in high school male futsal teams in Blora Regency. There was an interaction between training methods and agility towards the dribbling speed in high school male futsal players in Blora Regency. There was a different influence between the high and low agility towards the dribbling speed in high school male futsal players in Blora Regency. There was an interaction between training methods and agility towards the dribbling speed in high school male futsal players in Blora Regency.